Leibniz’s vision on Wallis’ infinite product - Raffo Quintana, Federico (ARFIL y UNL, 2020)
In this paper I will examine Leibniz’s view on Wallis’ infinite product for the quadrature of the circle. I will particularly show that Leibniz conceived that Wallis’ result is not equivalent to his own one, since, according to Leibniz, the infinitization of the product of the British mathematician implies an absurd. Thus, Leibniz’s conception, that his own proposal of an exact arithmetical quadrature of the circle has no precedent, would be justified.